Minimum Void Ratio Model Established from Tailings and Determination of Optimal Void Ratio - Shibo Li; Hao Liang; Hao Li; Jianquan Ma; Bin Li (Geofluids)
Minimum void ratio of tailings and its value change with fine content and are key design parameters for tailing consolidation and seepage stability. Based on the distribution of tailing grains with the sedimentary beach, we establish a minimum void ratio model for tailing grain in binary size, which requires only two parameters (ε and ω). Calibrations of the model using 168 groups of tests (22 kinds of grain size ratios with 7-9 kinds of fine contents) show two parameters that are fitting for power function, and the exponent values increase with the dominant grain size expanded. Besides, the exponent values are related to the equivalent grain size ratio, dominant grain size, and shape characteristics. The minimum void ratios with fine content are predicted under the derived model. Good agreement was obtained between the predictions and measurements, and the average discrepancies are less than 10%. And optimal void ratio and optimal fine content can be predicted, and the values are in good agreement with the experimental ones. Furthermore, based on the predicted optimal void ratio, the exponential relationship between the optimal void ratio and the equivalent grain size ratio may have no influence on the derived dominant grain size and shape characteristics. For tailings, further work is needed to verify if the derived exponential relationship between the optimal void ratio and the equivalent grain size ratio is valid.